THE INFLUENCE OF WORKLOAD, JOB PLACEMENT, AND CAREER DEVELOPMENT ON EMPLOYEE JOB SATISFACTION (Case Study at PT. Sinergi Inti Deksa Kuala Tanjung) - Richard Gultom; Ivana Supi Al Mudi; Fahrizal Perangin Angin; Willy Cahyadi; Rumiris Siahaan (CV. RADJA PUBLIKA, 2024)
This research aims to determine the influence of workload, work placement and career development on employee job satisfaction (case study at Pt. Sinergi Inti Deksa Kuala Tanjung). The research method used is a quantitative method using SPSS version 25.00, which was collected from the results of distributing questionnaires to PT employees. Deksa Kuala Tanjung Core Synergy as many as 67 respondents. The analytical method used in this research is using instrument tests, namely validity and reliability tests. Classic assumption tests are normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing namely T test and path analysis. The results of SPSS in this research are that the incentive variable (X1) has an effect on the workload variable which has an effect on job satisfaction, meaning that work placement has an effect on job satisfaction, career development has no effect on job satisfaction, workload, work placement and career development have a simultaneous effect on job satisfaction.